IPTEKS PENGENDALIAN PEMBIAYAAN PADA DEPARTEMEN UNIT DI PT. ASTRA INTERNATIONAL ISUZU SALES OPERATION CABANG MANADO - Kumaat, Victoria; Pusung, Rudy J. (Universitas Sam Ratulangi, 2018)
PT Astra Isuzu Manado branch is part of PT Astra International Tbk, which operates in the automotive business line, which has 3 departments, the first is the unit department, service department, and spare parts department. In the unit department itself has 3 types of customers, the first retail customers, fleet customers, GSO customers. In order to be able to carry out financing controls appropriately in the department of the PT Astra Isuzu branch of Manado, the accuracy and consistency of employees in the company is needed, while the five elements must be carried out by the company to achieve good financing control by using, controlling the environment. , risk measurement, activity control, information and communication, and supervision. In the following cases, PT Astra International has sufficiently carried out financing controls well enough to reach a better company that must improve financing controls more thoroughly in controlling the repayment of customers before maturity.Keywords: internal control, financial control, financial institutions